ALK-rearranged and EGFR wild-type lung adenocarcinoma transformed to small cell lung cancer: a case report - Chen, Rui; Jian, Yan; Liu, Yuzhen; Xie, Junping (Frontiers in Oncology, 2024)
Background： Cases of ALK rearrangement EGFR wild-type lung adenocarcinoma (LUAD) transforming into small cell lung cancer (SCLC) are rarely reported, and diagnosis is often delayed. The emergence of this transformation phenomenon is often regarded as a consequence of acquired resistance mechanisms. Case presentation ： A 47-year-old male diagnosed with poorly differentiated adenocarcinoma of the right middle lung (pT2N2M0, stage IIIA) achieved a 46-month progression-free survival (PFS) following surgery and adjuvant chemotherapy. During routine follow-up, tumor recurrence and metastasis was detected. Genetic testing revealed ALK rearrangement and wild-type EGFR, prompting treatment with ALK-TKIs. In May 2023, abdominal CT scans showed significant progression of liver metastases and abnormal elevation of the tumor marker NSE. Immunohistochemical results from percutaneous liver biopsy indicated metastatic SCLC. Results ： After resistance to ALK-TKIs and transformation to SCLC, the patient received chemotherapy combined with immunotherapy for SCLC, but the patient's disease progressed rapidly. Currently, the patient is being treated with albumin-bound paclitaxel in combination with oral erlotinib and remains stable. Conclusion ： Histological transformation emerges as a compelling mechanism of resistance to ALK-TKIs, necessitating the utmost urgency for repeat biopsies in patients displaying disease progression after resistance. These biopsies are pivotal in enabling the tailor-made adaptation of treatment regimens to effectively counteract the assorted mechanisms of acquired resistance, thus optimizing patient outcomes in the battle against ALK-driven malignancies.